A field incubation approach to evaluate the depth dependence of soil biogeochemical responses to climate change. Issue 3 (9th November 2022) - Guo, Xiaowei; Mao, Xiali; Yu, Wu; Xiao, Liujun; Wang, Mingming; Zhang, Shuai; Zheng, Jinyang; Zhou, Hangxin; Luo, Lun; Chang, Jinfeng; Shi, Zhou; Luo, Zhongkui
Abstract: Soil biogeochemical processes may present depth‐dependent responses to climate change, due to vertical environmental gradients (e.g., thermal and moisture regimes, and the quantity and quality of soil organic matter) along soil profile. However, it is a grand challenge to distinguish such depth dependence under field conditions. Here we present an innovative, cost‐effective and simple approach of field incubation of intact soil cores to explore such depth dependence. The approach adopts field incubation of two sets of intact soil cores: one incubated right‐side up (i.e., non‐inverted), and another upside down (i.e., inverted). This inversion keeps soil intact but changes the depth of the soil layer of same depth origin. Combining reciprocal translocation experiments to generate natural climate shift, we applied this incubation approach along a 2200 m elevational mountainous transect in southeast Tibetan Plateau. We measured soil respiration ( Rs ) from non‐inverted and inverted cores of 1 m deep, respectively, which were exchanged among and incubated at different elevations. The results indicated that Rs responds significantly ( p < .05) to translocation‐induced climate shifts, but this response is depth‐independent. As the incubation proceeds, Rs from both non‐inverted and inverted cores become more sensitive to climate shifts, indicating higher vulnerability of persistent soil organic matter (SOM) to climate change than labile components, if labile substrates are assumed to be depleted with the proceeding of incubation. These results show in situ evidence that whole‐profile SOM mineralization is sensitive to climate change regardless of the depth location. Together with measurements of vertical physiochemical conditions, the inversion experiment can serve as an experimental platform to elucidate the depth dependence of the response of soil biogeochemical processes to climate change. Abstract : We propose an innovative, simple and cost‐efficient field incubation approach to manipulate the depth of the soil layer of same depth origin, but keeping soil intact. This approach can be used to explore the depth‐dependence of the response of soil biogeochemical processes to climate shifts and elucidate underlying mechanisms.